(untitled) (ouvirOUver, 2015)
Este artigo pretende discutir sobre as potencialidades da formação superior em Dança e também da Arte como um dos lugares que se instaura a produção de conhecimento da área tanto no campo da obra artística quanto do ensino, o que vem estabelecer a atuação não somente do artista ou docente, mas do artista-docente que ocupa um lugar entre estes dois mundos, que são complementares e díspares. É preciso compreender este novo contexto, em que não se estabelece a presença de um diretor, coreógrafo, ou intérprete-criador de Cias, coletivos ou artistas independentes, mas se potencializa agente formador do híbrido que se instaura entre o contexto artístico e o ensino-aprendizagem, repercutindo no processo de formação humana enquanto indivíduo e coletivo que somos. ABSTRACT This paper aims to discuss about the potentialities of the higher education in Dance and Arts as one of the places that establish the knowledge production in the area, both in the field of artistic work as in teaching, which set the acting not only of the artist or the professor, but of the artistÂ¬-professor who occupies a place between these two worlds that are complementary and diffeÂ¬rent at the same time. What is required is to understand this new context, which not establishes the presence of the director, the choreographer, or the performer-creator of the Companies, colÂ¬lectives or independent artists, but it is potencialized as an agent capable to produce hybridity that is established between both contexts, the artistic and the learning-teaching, influencing on the process of human development as individual and collectiveness that we are. KEYWORDS Artist-Professor, higher education, university, dance